2016
DOI: 10.1055/s-0035-1561503
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Bromination of Aromatic and Heteroaromatic Compounds

Abstract: This review covers recent advances in C-H bromination of aromatic substrates. Transition-metal-catalyzed/-mediated reactions and transition-metal-free methods are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 108 publications
0
35
0
Order By: Relevance
“…A notable effort has been devoted towards the development of synthetic procedures for the preparation of aryl halides, particularly after the emergence of transition metal‐catalyzed coupling reactions, most of which require an aryl bromide as substrate . Although both nucleophilic and electrophilic bromination reactions are known, traditional approaches of nucleophilic bromination of arenes have limited substrate scopes and require harsh reaction conditions .…”
Section: Methodsmentioning
confidence: 99%
“…A notable effort has been devoted towards the development of synthetic procedures for the preparation of aryl halides, particularly after the emergence of transition metal‐catalyzed coupling reactions, most of which require an aryl bromide as substrate . Although both nucleophilic and electrophilic bromination reactions are known, traditional approaches of nucleophilic bromination of arenes have limited substrate scopes and require harsh reaction conditions .…”
Section: Methodsmentioning
confidence: 99%
“…We recently demonstrated that metal triflimide catalysis could be used to activate N ‐iodosuccinimide (NIS) for regioselective iodination of arenes and so a similar procedure was used to investigate bromination (Scheme ) . A mixture of iron(III) chloride (5 mol %) with the inexpensive ionic liquid 1‐butyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)imide ([BMIM]NTf 2 ), which forms the powerful Lewis acid Fe(NTf 2 ) 3 in situ, was found to activate N ‐bromosuccinimide (NBS) for the rapid and efficient bromination of a wide range of anisoles, phenols, anilines and acetanilides under mild conditions . Arenes with strongly deactivating groups (e.g., 1 l and 1 m ), naphthalenes ( 1 q and 1 r ) and 2,3‐benzodihydrofuran ( 1 s ) were all tolerated as substrates for effective bromination.…”
Section: Figurementioning
confidence: 99%
“…Among many halogenating agents, CuBr 2 has been widely used in bromination and in other organic reactions . Contrasting with the great use of the free salt, few examples of bromination with CuBr 2 complexes are found in the literature .…”
Section: Introductionmentioning
confidence: 99%